Determinants of International Stock Listings:: New Evidence - Ngassam, Christopher (Journal of Comparative International Management)

(untitled) (Management Futures, 2001)
This study reports the results of a survey of managers of NYSE-listed firms whose stocks became listed on one or more of the following exchanges - London's International Stock Exchange (ISE), Frankfurt Stock Exchange (FSE), and Tokyo Stock Exchange (TSE). The results show much similarity between the motives of NYSE firms for listing on these three exchanges. The key motives include increasing visibility, broadening the shareholder base, and gaining access to financial markets. Most respondents perceive few initial barriers to listing on the ISE and FSE, but the situation differs on the TSE. Respondents saw cost and disclosure requirements as initial barriers, but they decided to list their firms' stock anyway.